An Infinity of Relics: Erasmus and the Copious Rhetoric of John Calvin's Traité des reliques. (2021) - Weinreich, Spencer J.
Abstract : John Calvin's "Traité des reliques" (1543) inventories early modern Europe's fraudulent relics. Yet, theologically speaking, authenticity is irrelevant: all relics are idols to the evangelical Protestant, while for Catholics prayer's intention, not its conduit, was paramount. This article locates a solution in Calvin's humanist formation: chiefly, his debt to Desiderius Erasmus—not to Erasmus's satirical or devotional works, but to his rhetorical theory of copia . The "Traité" amasses a copia, an abundance, of fakes, burying the cult of relics in its own contradictions. Fusing rhetoric and proof, this mass juxtaposition subjects sacred presence to noncontradiction, patrolling vital confessional borders in Reformation theology.